A Syntactic Analysis Of Sentence Pattern Used In Westlife’s Song Lyrics - Fuad, Ulfa Muthi'ah; Setia, Eddy; Nasution, Ely Hayati (Politeknik Harapan Bangsa Surakarta, 2022)
This study aims to analyze about sentence patterns that used in westlife’s song lyrics. It was qualitative descriptive research with tree diagram theory by Bornstein. The data source of this study is Westlife album entitled Coast to Coast produced in 2000. To collect the data, the writer choose three songs lyrics such as My Love, I Lay My Love on You and I Have a Dream. The findings of this research were in the first song My Love there are 5 types of sentence patterns S àNP + VP (10 data), SàVP + NP (3 data), SàCP + NP + VP (3 data), SàAdv. P + NP + VP (2 data), Sà PP+ NP (7 data). In the second song I Lay My Love on You there are 6 types of sentence patterns SàAdv.P + NP + VP (2 data), SàNP + VP (10 data), SàCP + NP + VP (1 data), SàNP + CP +NP (2 data), SàAdj.P + VP (1 data), Sà PP + NP + VP (2 data). In the third song I Have a Dream there are 4 types of sentence patterns SàNP + VP (13 data), SàVP + NP (2 data), SàCP + NP + VP (4 data), SàAdj.P + CP + NP (1 data).